Quantifying floridean starch storage patterns in Arctic rhodoliths: blue carbon implications - Gabsteiger, Milane; Pyko, Ines; Wisshak, Max; Teichert, Sebastian (Polar research, 2025)
Rhodoliths composed of crustose coralline algae (CCA) are marine calcifiers of global significance. Here, we investigate how floridean starch storage patterns of Arctic rhodoliths from Svalbard are affected by environmental conditions. Quantifying the amount of starch in photomosaic scans of rhodolith slabs via amylopectin–iodine complex formation, we found that shallow water rhodoliths contain significantly higher starch percentages compared to the deeper-water dwellers. We conclude that the observed starch patterns are mainly controlled by water depth because light and rhodolith turnover frequency both decrease in deeper waters. Regarding rhodolith turnover, the occasional burial of turned rhodoliths in deeper waters can result in a dieback of the outer CCA thallus areas, which contain important starch supplies. As rhodoliths are both calcifiers and photoautotrophs, we highlight their relevance in potentially contributing to global blue carbon, that is, their role as a marine carbon sink. In this context, our quantification approach of floridean starch patterns in rhodoliths provides a straightforward basis for further studies on this topic.